ТӨВИЙН ХОВОР МЕТАЛЫН ОРДЫН ЧУЛУУЛГИЙН ХУВИРАЛ БА ХҮДРИЙН ЭРДЭСЛЭГ БҮРЭЛДЭХҮҮН - Д., Доржготов; Л., Жаргал; Б., Тамир; Ю., Туяацэцэг (Geological Issues, 2022)
The Tuv property is a greisen-type deposit hosted in NE-directed larger alteration zone. The deposit is developed within lithium-fluorine granitoid of Middle-Late Jurassic Sharkhad intrusive complex east of the Egzur rare metal ore knot. The greisen is characterized by quartz-albite-muscovite-protolitionite, quartz-muscovitetopaz-albite-lepidolite-zinnwaldite and quartz-muscovite-protolitionite and forms a larger succession/layer/sequence/strata. The rare metallic ore bodies create dykes and lenses inside the greisen which is composed of quartz-muscovite-topaz-albite-lepidolite-zinnwaldite. The lithium mineralization is also identified to be evenly distributed in all types of greisen. It is relatively independent. The rare metallic and rare elemental mineralization of the target deposit takes place through many stages of development; thus, the ore is very complicated in mineral composition. The key minerals of the ore are cassiterite, wolframite, and beryl. The rare metallic ore is divided into two types: beryl-tin-tungsten and beryl-tungsten. The Egzur and Sharkhad assemblages of the Nukhetdavaa ore district are considered to be highly prospective for lithium-fluorine granitoid –related rare metal deposition and lithium deposition. Therefore, it is recommended to conduct further surveys.